Clinical Pharmacology Of Immunocorrector Drugs (Texas Journal of Medical Science, 2025)
The concept, strategy and principles of immunocorrection and immunomodulatory therapy, pharmacological and immunobiological characteristics, mechanisms of action of immunomodulators of various natures, indications for their use are presented